Analisis Keahlian Auditor BPK-RI Menuju Pelaksanaan Fraud Auditing - Widayanti, Anna Retno; Subekti, Imam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2001)
The objective of this research was to analyze the expertise of Supreme Audit Board of Indonesia (BPK-RI), which related to the implementation of Fraud Auditing. The analysis was based on the data acquired from 147 respondents. The result showed that the audit expertise of Supreme Audit Board of Indonesia’s Auditor unconformity with the criteria of Fraud auditor. So, with this condition Supreme Audit Board of Indonesia is not ready for the implementation of fraud auditing yet. The other result showed that there are significant expertise differences between structural official and functional auditor in conformity with fraud auditor’s criteria. The most significant difference was in their knowledge and cognitive ability. The structural official expertise was better than the functional official. This is logical, because the structural officials usually become a team leader. Besides that, based on the expertise difference test, according the auditing scope, it was known that there are no significant expertise differences between employee in APBN, APBD/BUMD and BUMN sectors, in conformity with the Fraud auditor’s criteria. In addition, for the improvement of the expertise of supreme audit board of Indonesia’s auditor most of the respondents emphasize in the training quality improvement for the auditor. Keywords: fraud auditing, the expertise, task analysis, knowledge component, decision strategies, psychological traits, cognitive ability, ethical conduct.